Evaluation of micronuclei and antioxidant status in hospital radiation workers occupationally exposed to low-dose ionizing radiation - S. N. Mousavikia; M. T. Bahreyni Toossi; S. Khademi; M. Soukhtanloo; H. Azimian (BMC, 2023)
Abstract Purpose There is scientific evidence that ionizing radiation (IR) can be responsible for various health hazards that are one of the concerns in occupational exposure. This study was performed to evaluate DNA damage and antioxidant status in hospital workers who are occupationally exposed to low doses of IR. Materials and methods In this study, twenty occupationally exposed to low doses of IR (CT and angiography) comprising with control groups which matched them. In order to investigate the effects of chronic irradiation of radiation workers, Micronuclei (MN) frequency and the antioxidant activity of Superoxide Dismutase (SOD), Catalase (CAT) and Total Antioxidant Capacity (TAC) were measured. Then, to check adaptation against high challenge dose, the samples (in all groups) were irradiated in vitro and MN frequency was compared. Finally, to investigated the effect of the high dose after the acute and chronic low dose of ionizing radiation, MN frequency was compared in two groups (the control group that was to in-vitro irradiated (acute low dose + high dose) and radiation workers (chronic low dose + high dose)). Results MN frequency in the occupationally exposed group (n = 30) increased significantly when compared to the control group (p-value < 0.0001). However, chronic irradiation of radiation workers could not lead to an adaptive Sresponse, while acute low-doses could produce this effect (p-value ˂ 0.05). In addition, the activity levels of antioxidant enzymes SOD, CAT, and TAC were not statistically different between the radiation workers and the control group (p-value > 0.05). Conclusions We observed that exposure to low doses of IR leads to increased cytogenetic damage, could not cause an adaptive-response, and improve antioxidant capacity in radiation workers. Controlling healthcare workers' exposure is the first step to improving the health of hospital workers and the quality of patient care, thus decreasing human and economic costs.